2011
DOI: 10.5455/ijavms.20110802091129
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological Studies on Leptospirosis among Bovines in an Organized farm

Abstract: A total of 677 serum samples were collected from cattle and buffaloes with different clinical conditions and suspected for leptospirosis included abortion, repeat breeding, jaundice, haemorrhagic mastitis and apparently healthy animals, from a private farm in Gujarat state. The serum samples were subjected to seroprevalence studies using MAT. The seropositivity was found to be 34.74 per cent in cattle and 54.14 per cent in buffaloes. Among the 12 serovars against which the serum samples were screened, only fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 1 publication
8
8
1
Order By: Relevance
“…Thus, age was significantly influencing the seropositivity (p≤0.05). These findings indicated that increasing age of cattle makes them more prone to leptospiral infection and supported the findings of Kocabiyik and Cetin (2004) who also opined that seropositivity markedly increase with age and Balakrishnan et al (2011) mentioned that seropositivity was comparatively higher in the cattle of above 4 years of age. Contrary to this, Agrawal et al (2005) studied the seroprevalence in cattle, buffaloes and goats and reported that the seropositivity among cattle of 6-8 year age was 10% which decreased to 3% at the age of above 9 years.…”
Section: Species Breeds Districts Totalsupporting
confidence: 80%
See 3 more Smart Citations
“…Thus, age was significantly influencing the seropositivity (p≤0.05). These findings indicated that increasing age of cattle makes them more prone to leptospiral infection and supported the findings of Kocabiyik and Cetin (2004) who also opined that seropositivity markedly increase with age and Balakrishnan et al (2011) mentioned that seropositivity was comparatively higher in the cattle of above 4 years of age. Contrary to this, Agrawal et al (2005) studied the seroprevalence in cattle, buffaloes and goats and reported that the seropositivity among cattle of 6-8 year age was 10% which decreased to 3% at the age of above 9 years.…”
Section: Species Breeds Districts Totalsupporting
confidence: 80%
“…In the present study, the most prevalent serovar was Pomona (28.89%) as against earlier observations made by Balakrishnan et al [24] from this region who noted Serovar Hardjo to be most prevalent among cattle. In addition a number of serovars from time to time were reported from other states of India such as serovars Hardjo, Bataviae, Canicola, and Australis from West Bengal [13], Grippotyphosa, Pomona and ictrohemorhagiae from Andaman and Nicobar [22], Pomona, Hebdomandis, Medanensis, Hardjo, Andamana and Saxkoebing from Andhra Pradesh [26,27], Icterohaemorrhagiae and Grippotyphosa from Uttar Pradesh [28].…”
Section: Species Breeds Districts Totalsupporting
confidence: 69%
See 2 more Smart Citations
“…Generally, the crossbred cattle were more prone to any infection. Reports also suggested that leptospirosis was highly prevalent among the cross bred than the indigenous breeds (Balakrishnan et al., 2011). In contrary, (Agarwal et al, 2005) reported that the leptospirosis was more prevalent tin indigenous breeds than the cross bred.…”
Section: Resultsmentioning
confidence: 84%